Regulating periodontal disease with smart stimuli-responsive systems: Antimicrobial activity, immunomodulation, periodontium regeneration - Guang-Liang Su; Yu-Jun Peng; Hong-Ze Ruan; Juan Cheng; Tian Deng; Yu-Feng Zhang (Materials Today Bio)
Periodontal disease is a worldwide inflammatory condition that seriously affects both oral and systemic health. The presence of microbial biofilms and the dysregulation of the host immune response are considered crucial factors in the initiation and progression of periodontal disease. Mechanical debridement combined with antibiotic therapy is the standard non-surgical treatment for periodontal disease; however, this approach faces limitations in deep bacterial clearance and resistance to antibiotics. Although some new drugs and accessible nanodelivery systems have been developed, their targeting accuracy and drug utilization still require improvement in the complex oral environment. In recent years, intelligent biomaterials with stimuli-responsive characteristics have garnered more attention due to their unique advantages. These materials can respond to specific physiological signals or external stimuli, enabling precise release of functional agents. However, existing studies focus on the optimization of the single material system, lacking the horizontal comparisons and clinical evaluations of different stimulus-responsive materials. This review aims to address this gap by systematically examining the roles of endogenous and exogenous stimuli in regulating the periodontal disease progression and activating responsive substances. While various stimulus-regulated systems have their respective advantages, the complex oral environment necessitates synergistic action among multiple signals. The review further explores the applications of smart responsive materials in eradicating periodontal pathogens, regulating the inflammatory microenvironment, and promoting periodontium regeneration. Coordinated integration of functional mechanisms is crucial to achieving periodontal disease recovery. Moreover, the challenges faced by intelligent responsive materials in periodontal disease treatment are examined, along with outlining potential directions for future research. It outlines potential research directions to prioritize personalized material design, safety evaluations, and production quality control to advance clinical application.